Staged surgery for severe soft tissue and bone loss of the knee - Chan, C.K.; Goh, J.H.; Ng, W.M.; Kwan, M.K.; Merican, A.M.; Soong, K.L. (2010)
A 20- year-old female student was involved in a motor vehicle accident. She sustained a severe friction injury to the left knee that resulted in considerable soft tissue and bone loss. There was also damage to the knee extensor mechanism, tibialis anterior muscle, femoral trochlea, the anterior half of the tibial plateau extending distally to the proximal tibia and skin. However, there was no crushing of the limb or resultant neurovascular deficit but cancellous bone and the remainder of the joint were exposed. Repeated surgical debridement was performed and was followed by covering of the soft tissue using a latissimus dorsi free flap and skin grafts. The bony defect was reconstituted with antibiotic bone cement to prevent flap adherence and shrinkage, enhance stability and prevent fracture. The cement was later removed at the time of arthrodesis at which time an ipsilateral double barrel vascularised fibular graft supplemented with autogenously cancellous bone and a ring fixator was used. Computer tomography confirmed union at three months post procedure. The fixator was then removed and a tibialis posterior transfer was performed.